DIAGNOSTIC VALUE OF NON-CONTRAST HELICAL CT-SCAN AND INTRAVENOUS UROGRAPHY IN UROLITHIASIS EVALUATION - Hasan, Fadhli; Soebadi, Doddy M; Hardjowijoto, Sunaryo; Soebadi, Mohamad Ayodhia; Pria, Triyono Karmawan Sukmana; Pudjirahardjo, Widodo J (Indonesian Journal of Urology, 2015)
Objective: To evaluate the diagnostic value of Non Contrast Helical Computed Tomography (NCHCT) scanning as the first choice diagnostic modality for detecting urolithiasis cases in Soetomo General Hospital Surabaya and evaluate the feasibility as alternative to Intravenous Urography (IVU). Material & Methods: Seventeen patients with clinical manifestation of suspected urolithiasis underwent NCHCT and IVU to evaluate suspected urolithiasis. Reformatted three-dimensional CT was performed in all patients. The images were correlated with findings from surgical procedure (ureteroscopy, percutaneous nephrolithotomy, and open surgery). Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were determined for NCHCT and IVU. Results: The diagnosis of urolithiasis was defined as unequivocal evidence of urolithiasis on either NCHCT or IVU. Sixteen of seventeen patients evaluated were diagnosed with urolithiasis. NCHCT established the diagnosis in 16 of 17 patients while IVU was positive in 11 of 17 patients. IVU was negative in 6 of the 17 cases. The sensitivity, specificity and accuracy of NCHCT was 100%, 100%, and 100% respectively (p = 0.05) and the sensitivity, specificity, and accuracy of IVU was 68%, 100% and 70% respectively (p = 0.35). There was no statistically significant difference between IVU and NCHCT using Fisher’s exact test. Conclusions: NCHCT accurately diagnosed urolithiasis in patients with suspected urolithiasis. Considering that NCHCT is more effective and efficient than IVU as diagnostic modality in determining the presence of urolithiasis, it may be considered to replace IVU as the first line diagnostic tool for urolithiasis in Soetomo General Hospital Surabaya. Keywords: Non Contrast Helical CT Scan, Intravenous Urography, Urolithiasis.